Sustainability of the Toraja Arabica coffee value chain in Indonesia: economic, cultural, environmental, and certification dimensions - Azkar, Riad; Darma, Rahim; Amir, Ayu Anisa; Syam, Siti Hardianti; Kasim, Musliar; Bakheet Ali, Hamed Norolla; Amandaria, Riri; Astaman, Putra (Frontiers in Sustainability, 2025)
This study examines the Toraja Arabica coffee value chain as an integrated rural system in which economic, cultural, and environmental sustainability are closely intertwined. Using a qualitative case study approach, we conducted 21 semi-structured interviews, focus group discussions, and field observations with diverse actors including farmers, farmer groups, cooperatives, traders, processors, coffee shop owners, extension agents, government officials, and input suppliers. The data were thematically coded and interpreted through institutional, economic, and cultural lenses, with triangulation across methods, sources, and theories applied to strengthen credibility. The findings reveal that farmers face weak bargaining power in markets dominated by middlemen, whereas cooperative leaders struggle with governance and limited resources. Inconsistent postharvest practices and inadequate infrastructure further compromise product quality, and many farmers have voiced concerns about the erosion of cultural traditions linked to coffee rituals. Addressing these challenges requires strengthening cooperatives to improve bargaining power, upgrading infrastructure to ensure quality consistency, and promoting certification schemes and storytelling to valorize ecological stewardship and cultural identity. This study highlights the need for sustainability-oriented interventions that strengthen cooperatives, improve infrastructure and market access, promote postharvest innovations, and expand certification frameworks, demonstrating how value chains can be harnessed as pathways for inclusive and sustainable rural development.